2014
DOI: 10.1007/s10637-014-0126-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel antitumour indole alkaloid, Jerantinine A, evokes potent G2/M cell cycle arrest targeting microtubules

Abstract: Natural products play a pivotal role in the treatment of cancer; identification of compounds such as taxanes and the vinca alkaloids were seminal landmarks in natural product drug discovery. Jerantinine A, a novel Aspidosperma alkaloid isolated from plant species Tabernaemontana corymbosa, was previously reported to possess cytotoxic activity against vincristine-resistant nasopharyngeal carcinoma cells and is therefore an ideal candidate for biological investigation. Furthermore, Tabernaemontana corymbosa, has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
49
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 41 publications
8
49
0
Order By: Relevance
“…The 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyl tetrazolium bromide (MTT) assay was used as described 44 to assess the ability of test agents to inhibit cell growth and/or evoke cytotoxicity.…”
Section: Mtt Assaymentioning
confidence: 99%
“…The 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyl tetrazolium bromide (MTT) assay was used as described 44 to assess the ability of test agents to inhibit cell growth and/or evoke cytotoxicity.…”
Section: Mtt Assaymentioning
confidence: 99%
“…Amidst them, heterocycles with polycyclic ring system possess distinct rigid geometry displaying high functional specialization by orienting its substituents in three dimensional spaces, there by attracting great interest [2]. Indole is a bicyclic heterocyclic scaffold that find applications in medical therapy due to a variety of valuable biologic activities such as antiviral [3,4], antiinflammatory [5,6], anti-hyperlipidemic, antihypoglycemic, anti-hypertensive, anti-asthmatic, anti HIV [7], antidepressant [8] and notably anticancer [9][10][11][12][13][14][15] activity. Few marketed anticancer indole derivatives are vincristine, vinblastine, vinorelbine, vindesine, mitraphylline, cediranib and apaziquone [2].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the interruption of the cell cycle at the G2/M phase might be connected with antitubulin activity since the compounds that interact with microtubules interfere in the formation of the mitotic spindle and thus activate the spindle checkpoint. This results in a block in the cell cycle before the two daughter chromosomes divide …”
Section: Resultsmentioning
confidence: 99%
“…This results in a block in the cell cycle before the two daughter chromosomes divide. [46][47] Compounds that target microtubules and disrupt the normal function of the mitotic spindle have proven to be one of the best classes of cancer chemotherapeutic drugs since they are essential in several cellular functions. [48] In addition, these molecules can provoke vascular disruption in tumor cells, acting as antiangiogenic agents.…”
Section: Antiproliferative Activitiesmentioning
confidence: 99%